EPISTEMOLOGICAL LITERATURE STUDY OF ISLAMIC FINANCE - Bambang Lesmono; Sanusi Gazali Pane; M. Shabri Abd. Majid; Marliyah Marliyah; Rita Handayani (CERED Indonesia Institute, 2021)
This study examined research related to Epistemology of finance in national journal articles. The study used descriptive statistical analysis and narrative reviews based on 30 publication articles with the keyword